Sing to Jahweh!... Cursed be the day on which I was born! A paradoxical harmony in Jeremiah 20:7-18 - Bezuidenhout, L. C. (Hervormde teologiese studies, 1990)
The paradoxical juxtaposition of the statements ‘Sing to Jahweh!... Cursed be the day on which I was born!’ in Jeremiah 20:13 and 20:14 creates a tension which can be avoided if these two verses are isolated from each other by way of redaction criticism. In this article, the possibility and even appropriateness of respecting the relationship between these verses is explored. The segment 7-12 is regarded as a double lament. The segments 13 and 14-18 constitute two contrasting conclusions. This segmentation coincides with time-honoured divisions of the text. Verses 7-18 can be defined as an integral unit where an ironic symphony is created by a central metaphor of procreation and counterpointed radial metaphors of sexual abuse and childbirth.